Effects of deficit irrigation on the productivity of the common bean (Phaseolus vulgaris L.) - de Carvalho, José Joaquim [UNESP]; Saad, Joao Carlos Cury [UNESP]; Teixeira, Marconi Batista; Soares, Frederico Antonio Loureiro; da Silva, Nelmício Furtado; Di Campos, Melissa Selaysim; Cunha, Fernando Nobre; Dos Santos, Leonardo Nazário Silva (My University, 2018)
Although historically cultivated by small farmers, bean crops are now cultivated in large scale to increase productivity, which involves varied levels of technology in practices such as irrigation and direct sowing, as well as developed soil management and traditional practices. Along with the adoption of these techniques, an increase in irrigation efficiency has occurred, which aims to meet the water requirements of the crop throughout its life cycle without water wastage. The main objective of this study was to study the effects of different irrigation depths during two phases of the bean crop cycle and the behavior of cv. IAC-Alvorada during winter in the first and second year of direct sowing in Botucatu – SP, a southeastern region of Brazil. The experimental soil was classified as a red distroferric nitosol with a clayey texture. The delineated experimental design consisted of complete randomized blocks (each: 1.8×4.0 m), 16 treatments, and a witness with four replications. Irrigation treatments were performed daily with the assistance of a Class A tank. The following characteristics were evaluated: the productivity of the grains, number of pods per plant, number of grains per plant, number of grains per pod, grain yield, weight of 100 grains, empty pods per plant, and water use efficiency. The number of pods and the grain yield decreased with an increase in water stress at a 5% probability. Reductions in the applied water depth in the vegetative phase did not interfere with grain productivity. Reductions in water in the reproductive phase had the greatest effect on the productivity of grains and the number of pods per plant. The highest productivity was 3,322.27 kg ha-1 and resulted from the combination of an application depth of 40% in the vegetative phase and 100% in the reproductive phase.
Keywords: Red distroferric nitosol; Water stress; Water use efficiency